2017
DOI: 10.1016/j.nmni.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide prevalence of Rickettsia felis infections in patients with febrile illness in Bangladesh

Abstract: From July 2015 to December 2016, the presence of rickettsial pathogens was investigated for 414 patients with unknown fever in eight places in all the divisions of Bangladesh. Rickettsia felis was identified in blood samples from all the regions (overall detection rate, 19.6%), suggesting nationwide prevalence of R. felis infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The presence of rickettsial pathogens was investigated in eight places in all the divisions of Bangladesh. 15 In the present study, (26.1%) cases were confirmed among three bio-groups of rickettsial diseases by IFA from direct sera in febrile ill patients. The most frequent bio-group (35%) was typhus group followed by (32.5%) were scrub typhus group and (25%) were spotted fever group and (7.5%) were intermediate group (TG/ SFG) of rickettsioses.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The presence of rickettsial pathogens was investigated in eight places in all the divisions of Bangladesh. 15 In the present study, (26.1%) cases were confirmed among three bio-groups of rickettsial diseases by IFA from direct sera in febrile ill patients. The most frequent bio-group (35%) was typhus group followed by (32.5%) were scrub typhus group and (25%) were spotted fever group and (7.5%) were intermediate group (TG/ SFG) of rickettsioses.…”
Section: Resultssupporting
confidence: 63%
“…2 There are few available published data regarding the presence of rickettsial diseases from Bangladesh are also found. 3,4,14,15 Rickettsial diseases are the oldest known vectorborn diseases 6 and may cause serious public health problems. Morbidity and mortality rates vary among various types of rickettsial diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 108 In more recent years, there have been increasing reports of circulating R. felis DNA from febrile patients in sub-Saharan Africa 109–111 and Asia. 112 , 113 Interestingly, when control subjects have been added to similar investigations, R. felis DNA has also been found from non-febrile controls as well as those with fever. 114 , 115 Molecular detection of the organism has been reported from skin lesions of patients as well as from swabs taken from the skin of healthy subjects.…”
Section: The Curious and Controversial Epidemiology Of Flea-borne Spomentioning
confidence: 92%
“…Well-Felix is a nonspecific agglutination test which detects anti-rickettsial antibodies in patient's serum. Well-Felix test is based on crossreactions which occur between antibodies produced in acute rickettsial infections with antigens of OX (OX 19, OX 2, and OXK) strains of Proteus species 4 . The Well-Felix test can be done as either a slide or a tube test.…”
Section: Introductionmentioning
confidence: 99%
“…Islam MA and his colleagues found that Brucella prevalence was (2.5-18.6) % in Bangladesh 16 . Chowdhury et al17 found Rickettsia felis in blood samples from all the regions in Bangladesh was 19.6% cases. In this study Brucella species was not found, it may be due to patients attended at OPD may not have history of contact with domestic animals.…”
mentioning
confidence: 98%